Analysis of the current situation and risk factors of frailty in elderly patients with type 2 diabetes (老年2型糖尿病患者衰弱现状及影响因素分析) - LI Li (李莉); YING Yanping (应燕萍) (中西医结合护理)
Objective This study aims to investigate the current status of frailty in elderly patients with type 2 diabetes and analyze potential influencing factors. Methods A convenience sampling method was used to select 120 elderly patients from the Endocrinology Department of the First Affiliated Hospital of Guangxi Medical University as research subjects. Sociodemographic information, lifestyle, disease-related information, and other data were collected. The Fried Frailty Scale was utilized to assess the patients' frailty status, dividing them into frail and non-frail groups. Nutritional status and depression were evaluated using the Mini-Nutritional Assessment Short Form and the Short Geriatric Depression Scale, respectively. The findings of this study aim to provide a basis for related intervention research. Results The study found that 22. 50% (27/120) of participants experienced asthenia. Univariate analysis demonstrated significant disparities between the frailty group and non-frailty group concerning marital status, duration of night sleep, exercise habits, depression levels, nutritional status, and cognitive function (P＜0. 05). Multivariate regression analysis indicated that depression (OR=15. 526, 95%CI3. 264-73. 853) and cognitive impairment (OR=14. 335, 95%CI1. 791-114. 741) emerged as autonomous risk factors for frailty in elderly individuals with type 2 diabetes; Night sleep duration exceeding 6 hours (OR=0. 247, 95%CI0. 075-0. 819) and regular physical activity (OR=0. 088, 95%CI0. 020-0. 396) were identified as protective factors (P＜0. 05). Conclusion Elderly patients with type 2 diabetes have a higher incidence of frailty. Factors such as sleep duration at night, depression, regular exercise, and cognitive impairment can be targeted for intervention. Screening elderly patients with type 2 diabetes for early signs of frailty and addressing risk factors through specific interventions can help slow down the progression of frailty. (目的 调查老年2型糖尿病患者的衰弱现状, 分析潜在影响因素, 以期为相关干预研究提供参考依据。方法 通过采用方便抽样法, 选择广西医科大学第一附属医院内分泌科收治的120名老年患者作为研究对象, 收集社会人口学资料、生活方式、疾病相关资料等数据, 并使用Fried衰弱量表对患者的衰弱状况进行评估, 并将其分为衰弱组和非衰弱组, 采用微型营养评定简表、简版老年抑郁量表调查患者的营养状况、抑郁情况。采用单因素、多因素Logistic回归分析探究老年2型糖尿病患者衰弱的影响因素。结果 老年2型糖尿病患者衰弱的发生率为22. 50% (27/120)。单因素分析结果显示, 在婚姻状况、夜晚睡眠时长、运动情况、抑郁情况、营养状况、认知障碍等方面, 衰弱组和非衰弱组之间存在显著差异(P＜0. 05); 而在其他因素如性别、年龄、宗教信仰、学历、个人月收入等方面, 差异无统计学意义(P＞0. 05)。多因素回归分析结果显示, 抑郁(OR=15. 526, 95%CI: 3. 264~73. 853)和认知障碍(OR=14. 335, 95%CI: 1. 791~114. 741)是影响老年2型糖尿病患者发生衰弱的独立危险因素, 夜晚睡眠时长＞6 h(OR=0. 247, 95%CI: 0. 075~0. 819)和规律运动(OR=0. 088, 95%CI: 0. 020~0. 396)是其保护因素(P＜0. 05)。结论 老年2型糖尿病患者衰弱的发生率较高, 夜晚睡眠时长、抑郁情况、规律运动和认知障碍是潜在干预靶点。临床应对老年2型糖尿病患者进行早期衰弱筛查, 并针对衰弱发生的危险因素进行早期干预, 进而延缓衰弱的发展。)